L’enseignement du fait religieux : une enquête dans trois collèges - Sébastien Urbanski (Recherches en Éducation)
The article presents the results of a survey which aims to investigate teachers’ opinion about the ministerial project of “teaching religious fact(s)”. A short quantitative part puts forward some exploratory hypotheses about a possible influence of religious belief and seniority on the expressed viewpoints. A qualitative part identifies some controversial subjects, for instance: what is cultural and what is collective in the religious fact? Is the teaching of religious fact(s) in itself a means of education to tolerance? More generally, the article shows that there remains some opposition to the ministerial project. This raises the question of the effective implementation of curriculum.